2012
DOI: 10.3390/molecules17066348
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Phthalocyanine Labelled Polyethylene Glycol: Preparation, Characterization, Interaction with Bovine Serum Albumin and Near Infrared Fluorescence Imaging in Vivo

Abstract: Zinc phthalocyanine labelled polyethylene glycol was prepared to track and monitor the in vivo fate of polyethylene glycol. The chemical structures were characterized by nuclear magnetic resonance and infrared spectroscopy. Their light stability and fluorescence quantum yield were evaluated by UV-Visible and fluorescence spectroscopy methods. The interaction of zinc phthalocyanine labelled polyethylene glycol with bovine serum albumin was evaluated by fluorescence titration and isothermal titration calorimetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
1
18
0
1
Order By: Relevance
“…Zinc phthalocyanine conjugated PEG was synthesized by the substitution reaction of 4-chlorophthalonitrile and PEG . Then, zinc phthalocyanine conjugated PEG (1 g) and ε-CL (1 g) were polymerized under the catalysis of Sn­(Oct) 2 (0.1 g) in a polymerization tube under vacuum at 120 °C for 24 h. The mixture was dissolved in dichloromethane and then precipitated with cold petroleum ether, filtrated, and dried to provide the PCL–PEG–PHA–PEG–PCL copolymer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc phthalocyanine conjugated PEG was synthesized by the substitution reaction of 4-chlorophthalonitrile and PEG . Then, zinc phthalocyanine conjugated PEG (1 g) and ε-CL (1 g) were polymerized under the catalysis of Sn­(Oct) 2 (0.1 g) in a polymerization tube under vacuum at 120 °C for 24 h. The mixture was dissolved in dichloromethane and then precipitated with cold petroleum ether, filtrated, and dried to provide the PCL–PEG–PHA–PEG–PCL copolymer.…”
Section: Methodsmentioning
confidence: 99%
“…We developed several zinc phthalocyanine fluorescent probes for tumor imaging. , The results demonstrated that zinc phthalocyanine conjugated compounds have favorable imaging effects with good biocompatibility. Zinc phthalocyanine labeled polyethylene glycol was prepared in our lab to track and monitor the in vivo process of polyethylene glycol, suggesting that zinc phthalocyanine labeled polyethylene glycol has good optical stability and high emission ability in the near-infrared region. Zinc phthalocyanines could become a novel label to track the carrier in vivo because of their beneficial fluorescence emission.…”
Section: Introductionmentioning
confidence: 99%
“…There is remarkable change of the emission maximum with the addition of lactose-substituted zinc phthalocyanine while weak change is seen with glucose-substituted zinc phthalocyanine. The changes in BSA fluorescence intensity are related to the saccharide-substituted phthalocyanines by the Stern-Volmer relationship [33]. The Stern-Volmer quenching constant k SV of glucose-substituted zinc phthalocyanine and lactose-substituted zinc phthalocyanine with BSA are 4.06 × 10 4 and 2.05 × 10 5 , respectively, which comes from the differences of their molecular structures.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc phthalocyanine conjugated PEG was synthesized by the substitution reaction and condensation of 4-chlorophthalonitrile and PEG. 28 Zinc phthalocyanine-PEG copolymer (0.2 g) and alginate (0.6 g) were dissolved in 50 mL of water, and EDC$HCl (0.5 mg) and DMAP (0.5 mg) were added to catalyze the reaction. Aer stirring for 24 h at room temperature, the mixture was precipitated with formaldehyde and ltered, and the solid was dried for 12 h at 30 C under vacuum to obtain the zinc phthalocyanine-PEG-alginate copolymer.…”
Section: Synthesis Of Zinc Phthalocyanine-peg-alginate Copolymermentioning
confidence: 99%
“…Zinc phthalocyanine labeled polyethylene glycol has recently been reported to track and monitor the in vivo process of polyethylene glycol in our group. 28 This suggests that zinc phthalocyanine could become a novel uorescent tag to monitor biomaterials in vivo because of its satisfactory near infrared uorescence emission.…”
Section: Introductionmentioning
confidence: 99%